Effect of lysin on the crystallization habit of copper chloride - Abrahão, Ibrahim Octavio; Miranda, Luiz Fernando Ribeiro de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
This paper deals with the crystallization habit of copper chloride obtained from the evaporation of an aqueous solution containing lysin. The 30 concentrations studied were the result of combining 6 concentration of lysin (0,005, 0,001, 0,005, 0,01, 0,05 and 0,1 g/plate) to 5 concentrations of copper chloride (0,125, 0,25, 0,5, 0,75 and 1,0 g/plate). The main conclusion is that the crystallization pattern is characteristic and can be recognized in crystals obtained from extracts in which the crystallogenetie effect of the aminoacid is dominant. The best concentrations were those combining 0,25 to 0,5 g/plate of copper chloride with 0,005 to 0,1 g/plate of lysin.